Restructuring arrangements of state electricity company (persero) through the formation of subholdings in company law - Nandari, Ni Putu Sawitri; Mahadewi, Kadek Julia; Rusmana, I Putu Edi; Puspadewi, Anak Agung Ayu Intan (Institute Of computer Science (IOCS), 2024)
Law Number 40 of 2007 Concerning Limited Liability Companies, which coincides with the lack of regulation of the legal force of a subholding, which is a holding company in which another holding company owns the dominant stake. The goal is to discover and investigate the regulation about restructuring of the formation of subholdings of PT PLN (Persero), as well as to discover and investigate the impact of restructuring of subholdings of PT PLN (Persero) on their human resources. The normative legal research approach was applied in this study. The findings of this study revealed that the implementation of holding-subholding by PT PLN (Persero) is legally valid because a corporate action carried out in the context of company restructuring and in response to the request of the Minister of BUMN as the government representative as the GMS. The restructuring of Subholding PT PLN (Persero) has no substantial influence on human resources, and theres no legal certainty with the argumentum per analogium technique owing to the lack of Subholding rules in law. A distinct and specific legislative product is required for future company development to govern Holdingization. The government, as a regulator, must be committed to monitoring the execution of industrial relations